Comparison of two air sampling methods to monitor operating room air quality and assessment of air quality in two operating rooms with different ventilation systems in the national hospital of Sri Lanka - Tshokey, Tshokey; Somaratne, Pranitha; Agampodi, Suneth (International Journal of Infection Control, 2016)
Air contamination in the operating room (OR) is an important contributor for surgical site infections. Air quality should be assessed during microbiological commissioning of new ORs and as required thereafter. Despite many modern methods of sampling air, developing countries mostly depended on conventional methods.This was studied in two ORs of the National Hospital of Sri Lanka (NHSL) with different ventilation system; a conventional ventilation (CV) and a laminar air flow (LAF). Both ORs were sampled simultaneously by two different methods, the settle plate and sampler when empty and during use for a defined time period. Laboratory work was done in the Medical Research Institute.The two methods of sampling showed moderate but highly significant correlation. The OR with CV was significantly more contaminated than LAF when empty as well as during use by both methods. Overall, the difference in contamination was more significant when sampled by the sampler. Differences in contamination in empty and in-use ORs were significant in both ORs, but significance is less in LAF rooms. The consistent and significant correlation between settle plate and sampler showed that the settle plate is an acceptable method. The LAF theatre showed less contamination while empty and during use as expected. Air contamination differences were more significant when sampled with sampler indicating that it is a more sensitive method. Both CV and LAF ORs of the NHSL did not meet the contamination standards for empty theatres but met the standards for in-use indicating that the theatre etiquette was acceptable.